Metal oxides as transport layer for perovskite solar cells - Affonço, Lucas Jorge (2023)
Nowadays, perovskite solar cells draw great interest in the energy harvest field mainly due to the rapid increase in efficiency. Nevertheless, challenges like the stability improvement and the scalability of the layers must be surpassed. Although the perovskite layer is the center of the device, this layer alone could not reach such high performance. Transport layers are necessary and offer great aid for charge extraction, and device performance, unveiling the importance of those layers and the materials used, being those layers the focus of this work. Firstly, the niobium pentoxide deposition (electron transport layer) by slot die coating was investigated. The niobium pentoxide was presented as a viable alternative to the traditional titanium oxide, mainly due to a positive influence on the stability that might be seen through a reduction in the hysteresis. The slot die coating is an attractive solution-based deposition technique, as it allows the coating of a wide diversity of materials with high throughput, which can be favorable for large-scale production. For this goal, varied parameters were examined for the deposition process. Secondly, the usage of potassium chloride salt to mitigate the hysteresis effects between the transport layer and the perovskite was investigated, comparing its application as an additive in the perovskite precursor solution or as a passivation layer, in devices with tin oxide as transport layer. The layers were analyzed by microscopy, and the influence of the materials on the device performance was assessed using the J-V curves. Considering the slot die coating of the niobium pentoxide, the layers were successfully obtained, and the best devices reached about 12 % efficiency. Although the obtained efficiency is still low compared to the present high-performance devices, obtained through other depositions techniques less scalable and more expensive, so far, no report on the slot die coating of the niobium pentoxide for perovskite solar cells was found, For the passivation, its utilization resulted in negligible hysteresis effects. Thus, either as a layer or additive, the performances were similar. However, the outcomes indicate that the usage as an additive might be a handicap for the perovskite being more favorable to use as a passivation layer.